Hydrohumanities Water Discourse and Environmental Futures - De Wolff, Kim; Faletti, Rina C.; López-Calvo, Ignacio (University of California Press, 2021)
From drought to deluge, climate extremes are mobilizing humanities scholars to reimagine water discourse, which has until now largely focused on human power over water. This volume unites preeminent and emerging voices across humanistic disciplines to develop a new discourse called the hydrohumanities, dedicated to examining water-human-power relationships.;Organized into three themes in water studies-agency, fluid identities, and cultural currencies-Hydrohumanities exemplifies how interdisciplinary approaches can transform water conversations. Part One explores the properties of water and the ways water challenges human plans for control. Part Two explores how water (or its absence) shapes human collective and individual identities. Part Three engages notions of value and circulation to think about how water has been employed for local, national, and international gains. This volume shows how humanities scholarship has world-changing potential to achieve more just water futures.;"This fascinating essay collection breaks new ground with its interdisciplinary insights into the relations between water and human societies." MATTHEW GANDY, author of The Fabric of Space: Water, Modernity, and the Urban Imagination;"Water's power, purpose, and meaning cannot be contained by any one scholarly discipline. Understanding the value of water in a time of climate catastrophe demands more-than-human humanities, and Hydrohumanities answers this call." ASTRIDA NIEMANIS, author of Bodies of Water: Posthuman Feminist Phenomenology